Optimalisasi Manajemen Akun Youtube Untuk Meningkatkan Branding Dan Monetisasi - Rizaldi, Rizaldi; Putra, Guntur Maha; Kifty, Wan Mariatul (Civiliza Publishing, 2025)
YouTube is one of the leading platforms for personal branding and content monetization in the digital era. However, many creative individuals and Micro, Small, and Medium Enterprises (MSME) actors still lack optimal strategies for managing YouTube channels professionally. This community service program aimed to enhance participants' capacities in content production, channel management, audience engagement, and monetization strategies. The program involved 15 participants, with 80% showing significant improvement in technical understanding after training. A total of 5 YouTube channels were successfully optimized based on the training materials, with view counts increasing by 2–3 times within two weeks of implementation. A digital training module titled “Basic Video Production and YouTube Content Management for Beginners” was also developed and distributed. Additionally, the program targeted non-productive communities through training on digital literacy and responsible social media usage. Overall, this initiative effectively strengthened participants’ abilities to use YouTube as a platform for branding and sustainable income generation, while also supporting the advancement of technology based digital literacy.